APPLICATION OF HORIZONTAL TO VERTICAL SPECTRAL RATIO (HVSR) METHOD FOR SINGLE STATION MICROTREMOR ANALYSIS OF SOLOK MUNICIPALITY, WEST SUMATERA, INDONESIA - Fauziah Nur Aini, Sarah
Solok Municipality, West Sumatra Province experiences disasters quite often, therefore its disaster mitigation is a necessity, especially for policy makers and from a scientific perspective. The purpose of this research is to characterize the distribution of dominant frequency values (f0) and amplification factors (A0) with the Horizontal-to-Vertical Spectral Ratio (HVSR) Method and map seismic vulnerability areas based on the seismic vulnerability index (Kg) in Solok Municipality. The HVSR method is still widely used today because it is simple and inexpensive. The research was conducted using microtremor data obtained from 110 stations spread across Solok Municipality. Measurements were made from 12 pm to 6 pm with a sampling frequency of 100 Hz in a time span varying from 10 minutes to more than 1 hour. The microtremor data obtained was then processed using the HVSR method on Geopsy software so that the H/V curve was obtained which resulted in f0 and A0 values for each station. The research results obtained in the form of f0, A0, and Kg distribution maps in Solok Municipality. The resulting f0 values range from 0.53 to 4.93 Hz, A0 between 2.09 to 7.47, and Kg between 0.94 to 50.27 s2/cm. The highest Kg value is found at station S060, S070, S072, and S095 which is located north of Solok Municipality, with a lithology of volcanic material. Therefore, even though it is not located at the epicenter, Solok Municipality still has a risk of being affected by earthquakes, especially on the North side of Solok Municipality.